Tensile examination of progressive damage and failure in porous ceramic composite materials using the XFEM - Metehri, Aicha; Madani, Kouider; Mechab, Belaïd; Mokhtari, Mohammed; Ghermaoui, Ilias M.A. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Porosity is a significant factor that causes voids to become trapped in materials during composite material fabrication. This study is dedicated to modelling fracture modes within highly stressed areas of an advanced SiC/Cf component at a macroscopic scale. Methods: The finite element method is used to analyze defects within composites, considering factors such as porosity size, shape, and tensile stress. The Monte Carlo method predicts the distribution function (F). Results: Three pores are distributed across the width of the material, which reduces the active cross-sectional area of the material and, consequently, leads to a significant reduction in strength. Overall, resistance tends to decrease, with a more noticeable drop. Conclusion: It is concluded how the form and the size affect the failure load, employing the Extended Finite Element Method (XFEM) to predict mode-I fracture behaviour. The porosity parameter significantly affects the durability of the structure. It is noted that the size of pores (ϕ) is a crucial component that affects the distribution function (F). The variability in this parameter substantially elevates the likelihood of plate failure and diminishes the longevity of a structure.